STREET FURNITURE PEDESTRIAN DIJALAN DUKUH ATAS, STIABUDI JAKARTA SELATAN - Riyan Tri Hadriansyah; Zefri (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2020)
The need for space for pedestrians in the city of South Jakarta has begun to bedeveloped according to the needs and priority scale of the designation of the area in fulfillingthe space infrastructure and facilities for pedestrians. Pedestrian or pedestrian space is oneelement of the landscape that plays an important role in improving the visual quality of publicopen spaces. Arrangement of street furniture elements (furniture for pedestrians) withcharacter is needed to enhance the identity of the Dukuh Atas Setiabudi area, South Jakarta.The descriptive qualitative method of analysis was used as a study approach. Provision offacilities and infrastructure for pedestrians on the side of the road (sidewalk) and in the GreenOpen Space (RTH-green pathway) area, both pedestrian paths, green lanes, markers forpeople with disabilities (diffable), lighting, seats, places garbage, marker elements, bus stops,and drainage are designed to fulfill the concept of urban heritage tourism in Dukuh Atas,South Jakarta.